Synthesis and biological evaluation of novel 3,4-diaryl lactam derivatives as triple reuptake inhibitors - Park, Jung-eun; Song, Chiman; Choi, Keehyun; Sim, Taebo; Moon, Bongjin; Roh, Eun Joo (Pergamon Press Ltd., 2013)
A series of 3,4-diarylpyrrolidin-2-one was designed, prepared and evaluated as triple reuptake inhibitors for antidepressant. Most compounds exhibited comparable in vitro efficacy as norepinephrine and dopamine transporter reuptake inhibitors. Especially, 2i showed better potency than GBR-12909 (IC50 = 14 - nM) which was used as reference compound for dopamine transporter. In addition, 2a and 2b showed inhibition (5.17 mu M-85.6 nM) for three transporters. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: PHARMACOLOGICAL EVALUATION; MAJOR DEPRESSION; PROFILE; POTENT; AGENTS